Imaging evaluation of nano-hydroxyapatite/polyamide 66 strut in cervical construction after 1-level corpectomy: a retrospective study of 520 patients - Zhong, Weiyang (Eur J Med Res, 2020)
BACKGROUND: The application of nano-hydroxyapatite/polyamide 66(n-HA/PA66) struts has become reliable in anterior cervical corpectomy and fusion (ACCF) as a source of sufficient segmental stability. This was a retrospective and long-term imaging evaluation of the n-HA/PA66 strut in 1-level ACCF. METHODS: The patients between June 2006 and December 2014, who underwent 1-level ACCF using an n-HA/PA66 strut, were reviewed. The neurological status was assessed using the Japanese Orthopedic Association (JOA) score and axial pain was evaluated using a Visual Analogue Scale (VAS) score and the radiographic parameters were determined by X-ray and 3-D CT examinations when necessary for the evaluation of bone fusion using the Brantigan scale and imaging characteristics. RESULTS: A total of 520 patients underwent one-level ACCF, with a mean follow-up (FU) duration of 72.38 ± 24.56 months. The level of surgery was C4 in 58 cases, C5 in 173 cases, C6 in 208 cases, and C7 in 81 cases. According to the Brantigan scale, on X-ray examination, the bony fusion rate was observed to be 40%, 70%, 93%, and 98% at 3 months, 6 months, 1 year and the final FU. An interesting radiographic appearance of the bone graft growth pattern was classified into three types. 95% of the patients accounted for types a and b. No significant differences were observed in age, hospitalization duration, surgical haemorrhage volume, or fusion rate among the types except in the percentage and sex of the patients among the types. Type a had better cervical lordosis, and less subsidence than types b and c (P < 0.05). No significant difference was found in segment angle between type a and type b. Type c was more often observed with subsidence rate, segmental angle loss and cervical alignment loss than types a and b (P < 0.05). Type a also had a slightly higher fusion rate, than types b and c, but there were no significant differences. The overall mean JOA score at the final follow-up among the groups were significantly improved comparing that preoperatively and no significant differences were found among the groups, no matter pre-operation or final follow-up. The overall mean VAS score at the final follow-up among the groups were significantly improved comparing that preoperatively and no significant differences in preoperative VAS score were found among the groups. However, the VAS score at the final follow-up of type a or type b was better than type c. No patients received revision surgery. CONCLUSIONS: The type a bone graft growth pattern could allow a lower incidence of subsidence and better maintenance of local and global alignment to be achieved and is thus proposed for surgeons.